Трехмерная токовая интегральная модель магнитного поля электромагнитного перемешивателя - Евдокимов, В.Ф.; Кучаев, А.А.; Петрушенко, Е.И.; Кучаев, В.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
The scalar integral equations system, which equivalent current integral equation for the first symmetric component of rotating magnetic field of the electromagnetic stirrer is received. The system numerical solution is connected with big volume of the additional calculations since in it is not taken into account symmetries of the magnetic field of the first symmetrical component relative to coordinate planes.